2018
DOI: 10.21470/1678-9741-2017-0231
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Repair of Complex Aortopulmonary Window: A Case Study

Abstract: Aortopulmonary septal defect, also known as the aortopulmonary window, is a rare congenital macrovascular malformation. This case involves a 9-year-old boy with aortopulmonary septal defect (type I combined with type IV). Before surgery, milrinone and alprostadil were used to counteract high lung pressure. Surgery was performed under cardiopulmonary bypass, following which the pulmonary pressure decreased. The aorta was cut, and the right pulmonary artery opening was connected with the main pulmonary artery se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Among patients with complex APW, topsy-turvy heart, atrial septal defect, and VSD were the most frequently observed associated conditions (50%). In the case reports we reviewed, rare cardiovascular abnormalities were identified in association with APW, including a right aortic arch with an aberrant origin of the left subclavian artery (15), an isolated origin of the left subclavian artery from the left pulmonary artery (16), total abnormal pulmonary venous return (17), a right pulmonary artery originating from the ascending aorta (8), and crisscross pulmonary arteries (18). We have not encountered such rare abnormalities in our patients.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Among patients with complex APW, topsy-turvy heart, atrial septal defect, and VSD were the most frequently observed associated conditions (50%). In the case reports we reviewed, rare cardiovascular abnormalities were identified in association with APW, including a right aortic arch with an aberrant origin of the left subclavian artery (15), an isolated origin of the left subclavian artery from the left pulmonary artery (16), total abnormal pulmonary venous return (17), a right pulmonary artery originating from the ascending aorta (8), and crisscross pulmonary arteries (18). We have not encountered such rare abnormalities in our patients.…”
Section: Discussionmentioning
confidence: 78%
“…Early closure is imperative given the potential for rapid onset of congestive heart failure owing to high pulmonary blood flow. The conventional approach to treating APW is surgical intervention, and several studies (4,5,6,8,13,20) have examined surgical outcomes in this context. However, transcatheter closure may serve as a viable alternative in cases with no associated cardiovascular lesions and adequate rims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation